The Diagnostic Performance of Fluorescent Microscopy and MTB/RIF Assay Gene Xpert in Pulmonary Tuberculosis at Tertiary Care Hospital of Lahore - Mehwish Kiran, Syed Mazhar Ali Naqvi, Arslan Iqbal, Huma Batool, Abdur Rahman Zaheer Butt, Nazish Shafi, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To find out the diagnostic precision of GeneXpert and AFB smear by fluorescent microscope for diagnosis of pulmonary tuberculosis keeping the culture as a gold standard. Methodology: A survey performed in the Pulmonology and Pathology Department, Lahore General Hospital, Lahore. Patients of age 16-70 years, both genders presented with cough>2weeks, fever >99oF, and sputum, with radiographic findings constant with pulmonary T.B were included in this study. Patients previously diagnosed with PTB and on antibiotics within 2 weeks at the time of inclusion and patients having extrapulmonary TB were excluded from this study. Patients were asked to submit sputum samples in 2 containers, one having 2-3 ml and the other having 4-5 ml of sputum. The samples were proceeded according to SOPs for FM sputum microscopy, MTB/RIF assay & sputum culture. The collected data was analysed statistically with the help of SPSS version 20. Results: There were 100 patients included in this study with mean age of cases 42.66 ± 15.69 years. There were 59% male and 41% female, with a higher male to female ratio. 73% cases were positive on Gene Xpert, 68% on AFB smear, and 72% cases were positive on culture. The specificity, sensitivity, NPV, PPV & overall diagnostic accuracy of Gene Xpert was 71.43%, 90.28%, 74.07%, 89.04% and 85.00% and for AFB LED-FM microscopy was 86.11%, 78.57%, 91.18%, 68.75% and 84.00% respectively. Conclusion: Simple modality like fluorescent microscopy gave better results and diagnostic yield as compared to Zn microscopy. Gene Xpert MTB/RIF assay detected TB in very short time, and it is sensitive and accurate method along with detection of rifampicin resistance. However, more studies like that should be recommended as Pakistan is still at 5th number among high load diseased countries. The culture is always a gold standard method among all these sensitive and specific methods.